Avaliação da resposta tecidual de extratos de araçá (Psidium Cattleianum) associado ao hidróxido de cálcio: análise edemogênica e histológica em ratos - Valentim, Diego [UNESP] (2013)
Leaf extracts from 'araçá' (Psidium cattleianum) are biocompatible and when combined with calcium hydroxide [Ca (OH) 2] inhibits Enterococcus faecalis in 24 hours. This study aimed to evaluate the tissue respons of the 'araça' leaf extracts associated to Ca(OH)2 by edemogenic and histological analysis. Eighty male wistar rats weighing between 200 and 280g were used in this study. For edemogenic analysis, 30 animals were divided in 3 groups (n=10) - (a) aqueous 'araça' extract + Ca(OH)2; (b) ethanolic extract + Ca(OH)2; (c) propylene glycol + Ca(OH)2. Half of the specimens were evaluated after 3 hours and half after 6 hours. Under general anesthesia, 0,2ml/100g body weight of 1% Evans blue were injected in the penile vein. After 30 minutes, each studied substance was injected in the subcutaneous. Edemogenic analysis was performed though spectrophotometry (λ=630ηm) after 3 and 6 hours. For the inflammatory reaction evaluation, 50 rats were used. Each rat received 4 polyethylene tubes containing the studied substances and one empty tube (control). Evaluation periods were 7, 15, 30, 60 and 90 days. The tissues were stained with Hematoxylin and Eosin and scores were attributed for intensity of tissue response. The association of ethanolic extract to Ca(OH)2 presented larger edema after 3 hours than the other groups (p<0.05). After 6 hours there was no significant difference. On the histological analysis, an evolution on tissue repair was observed over time. The extract groups presented similar response to the Ca(OH)2 + propylene glycol and control. In conclusion that the use of guava extract as vehicle of Ca (OH)2 exhibit favorable tissue response as well as propylene associated with Ca (OH)2